Radiosensitization effect of iridium (III) complex on lung cancer cells via mitochondria apoptosis pathway - Pang, Yuru; Meng, Qiqi; Cui, Yangchen; Liu, Shiyi; Jiang, Huihui; Xu, Chenlan; An, Yan; Jiao, Yang; Zhang, Qi; Nie, Jihua (Frontiers in Pharmacology, 2025)
BackgroundLung cancer is the leading cause of cancer-related death in the worldwide. Although cisplatin and other platinum-based drugs are widely used as radiosensitizers in radiotherapy and considered the first-line treatment for advanced lung cancer, their clinical utility is often limited by drug resistance and severe cytotoxic side effects. In recent years, iridium-based complexes and other transition metal cation complexes with similar structural properties have garnered increasing research interest due to their potential anticancer properties.MethodsRecently, we synthesized a novel iridium (III) complex (Ir-1) and evaluated its safety and stability. The present study aimed to identify Ir-1 with potent anticancer activity by assessing its cytotoxic effects on lung cancer cells in vitro. Additionally, it investigated Ir-1's radiosensitizing efficacy and the underlying mechanisms.ResultsThe results demonstrated that Ir-1 exhibited significant radiosensitizing effects on lung cancer cells. Ir-1 effectively reduced cell viability and colony formation, arrested the cell cycle at the G2/M phase, inhibited cell migration and invasion, decreased mitochondrial membrane potential, and increased reactive oxygen species (ROS) generation in lung cancer cells. Importantly, these cytotoxic effects were selective, with minimal impact on normal cells. Mechanistic studies showed that Ir-1 enhanced radiation-induced cancer cell death by disrupting mitochondrial function and activating the mitochondrial apoptotic pathway. This was evidenced by upregulated expression levels of Bax, Cytochrome c (Cyt-C), and Caspase9 proteins, along with reduced level of Bcl-2 protein. Notably, the addition of a Cyt-C inhibitor significantly reduced the expression of Cyt-C and Caspase9 proteins. Similarly, treatment with the Caspase9 inhibitor Z-LEHD-FMK also reduced Caspase9 protein level.ConclusionThis study provides robust evidence that Ir-1 is a promising and safe radiosensitizer for lung cancer therapy. Its ability to enhance radiation-induced cytotoxicity through mitochondrial dysfunction and activation of apoptotic pathways highlights its potential for clinical application.